Weakly perturbed operator equations in Banach spaces - Zhuravlev, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We obtain the conditions of bifurcation of the solutions of weakly perturbed operator equations in Banach spaces from the point ε = 0 and propose a convergent iterative procedure for finding the solutions in the form of parts of the series in powers of ε with pole at the point ε = 0.